Mobile FeedApps to formulate chicken rations from locally available ingredients in Tanzania, Nigeria, and Ethiopia - CGIAR Research Program on Livestock (2019)
The Mobile Feed Apps are ready for use by farmers through poultry platforms established in Nigeria, Tanzania and Ethiopia. Future plans are to perform surveys to monitor farmer use of the apps to formulate their own feed.